Alternative paradigms of hospital work organisation and health provision - Oliveira, Teresa Carla (2007)
Health and hospital services have been under pressure to cut costs and increase efficiency in most European countries. This article analyses how organisational change in health care now is moving in two ways: either towards “internal markets” on the implicit presumption of widening choice for both providers and patients, or towards “internal flexibility” and efficiency gains based on explicitly aiming at mutual advantage for both patients and health service providers. It relates these paradigms to those which they mirror in the production sphere, including “Fordist” models of lowering costs in volume provision, and “post- Fordist” models of flexible work practices focussed on more customised quality provision of services. It suggests on case study evidence from the UK that “internal markets” and more Fordist health provision have increased patient throughput, but have not reduced costs or widened patient choice, while in key cases reducing the quality of patient service. It draws on other case studies of alternative “post-Fordist” models of hospital organisation as an example of how cost reduction can be achieved by focussing directly on patient flow and thereby also increasing the quality of patient care. It draws implications from these for alternative paradigms of flexibility-by-constraint and flexibility- by-consent in hospital and health provision, and relates these to proposals for innovation-by-agreement, lifelong learning and a better work-life balance as recommended by the Lisbon European Council in June 2000. Allowing for cultural differences, it submits also that the efficiency gains in hospital provision justify assessing whether a transition to flexible post Fordism on the basis of mutual advantage for patients and providers is feasible in Portugal, and draws attention to the degree to which continuous improvement has been achieved in Portugal in the production sphere.